1992
DOI: 10.1139/v92-374
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis and establishment of the absolute stereochemistry of (+)-mostueine. Addition of chiral nucleophiles to 3,4-dihydro-2-methyl-9-(p-toluenesulfonyl)-β-carbolinium iodide

Abstract: A highly convergent synthesis of the pentacyclic indole alkaloid (+)-mostueine (1) is described. The key step involved the coupling of the dianion derived from (1′S)-3-(1′-hydroxyethyl)-4-methylpyridine (4) with the iminium salt 3,4-dihydro-2-methyl-9-(p-toluenesulfonyl)-β-carbolinium iodide (3). Low asymmetric induction (15% de) at the C-1 position of the β-carboline ring system (C-3 of mostueine) was obtained. The nonfermenting baker's yeast-mediated reduction of 3-acetyl-4-methylpyridine provided the hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…At first, 3,4-dihydro-β-carboline ( 2 ) was allowed to react with acetone in the presence of ( S )-proline, and it was found that the substrate decomposed to a complicated mixture. Thus, 9-tosyl-3,4-dihydro-β-carboline ( 1 ) was selected as the next substrate.…”
mentioning
confidence: 99%
“…At first, 3,4-dihydro-β-carboline ( 2 ) was allowed to react with acetone in the presence of ( S )-proline, and it was found that the substrate decomposed to a complicated mixture. Thus, 9-tosyl-3,4-dihydro-β-carboline ( 1 ) was selected as the next substrate.…”
mentioning
confidence: 99%
“…To expand the collection with compounds bearing additional chiral centers, the same reaction was performed between the enantiopure octahydroindolo[2,3-a]quinolizine 3h and the 2,3-dihydroxybenzoic acid (34) to afford enantiomerically pure product 35f in good yield. The stereochemistry of compound 35f was confirmed from its 1D and 2D NMR spectra (pages S89−S92 of the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Diastereoselective Synthesis of Benzoxazepinone Fused to Octahydroindolo[2,3-a]quinolizine Scaffolds. To expand the scope of this reaction, the 2,3-dihydroxybenzoic acid (34) was replaced with 2,3-dihydoxy benzamide (36) (Scheme 9). Surprisingly, this reaction did not produce the expected compound 38, as was previously observed, but yielded the indolino benzoxazepinone derivative 37 instead.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of our research for the synthesis of chiral 1-substituted 1,2,3,4-tetrahydro-β-carboline derivatives, we found that 9-tosyl-3,4-dihydro-β-carboline ( 1 ) is a good substrate for the asymmetric addition of methyl ketones in the presence of ( S )-proline . We further investigated the reaction using various methyl ketone derivatives, and found that the use of 3-ethyl-3-buten-2-one resulted in concise asymmetric synthesis of ent -dihydrocorynantheol.…”
mentioning
confidence: 99%